2003
DOI: 10.1161/01.hyp.0000065387.09043.2e
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Depletion Increases Blood Pressure and Hypothalamic Norepinephrine in Middle-Aged Spontaneously Hypertensive Rats

Abstract: Abstract-In male spontaneously hypertensive rats (SHR) a high NaCl diet increases arterial pressure via a reduction in anterior hypothalamic nucleus norepinephrine release. Young female SHR are relatively well protected from this NaCl-sensitive hypertension, but depletion of both endogenous and dietary estrogens greatly exacerbates NaCl-sensitive hypertension. This study tests the hypothesis that estrogen also protects late middle-aged female SHR from NaCl-sensitive hypertension and that this effect is mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 32 publications
2
33
0
Order By: Relevance
“…In this regard, Cervenka et al (8) demonstrated increased sodium excretion following acute nNOS inhibition in intact but not denervated male mRen(2)27 rats, the founder strain to the current congenic strain. We do not know the status of the adrenergic system following ovariectomy in the mRen2.Lewis rat, although estrogen exerts an inhibitory influence on sympathetic activation (13,15,30,34). Moreover, estrogen depletion exacerbated the salt-dependent increase in blood pressure and renal injury (proteinuria) in the mRen2.Lewis rat, and altered NO levels in the kidney may well contribute to the sodium-sensitive phenotype (11).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Cervenka et al (8) demonstrated increased sodium excretion following acute nNOS inhibition in intact but not denervated male mRen(2)27 rats, the founder strain to the current congenic strain. We do not know the status of the adrenergic system following ovariectomy in the mRen2.Lewis rat, although estrogen exerts an inhibitory influence on sympathetic activation (13,15,30,34). Moreover, estrogen depletion exacerbated the salt-dependent increase in blood pressure and renal injury (proteinuria) in the mRen2.Lewis rat, and altered NO levels in the kidney may well contribute to the sodium-sensitive phenotype (11).…”
Section: Discussionmentioning
confidence: 99%
“…The other drawback to most of the menopausal studies in animals is that ovariectomy does not cause hypertension and increased CVD. Two contradictions to this statement are the SHR female that, when ovariectomized at middle age and placed on high-salt diet, becomes more hypertensive 44 and the young ovariectomized Dahl saltsensitive rat that exhibits increased blood pressure compared with intact females independent of salt diet. 45 There are now 3 animal models that have been described that develop progressive hypertension and CVD with aging that can be used to better determine the changes that occur after menopause.…”
Section: Estrogen: "Bad Girl"mentioning
confidence: 99%
“…Sheep, rabbits, nonhuman primates, rats, and mice have been used as models of various menopausal changes; 6 however, to our knowledge, there is no animal model of naturally occurring postmenopausal hypertension. There have been attempts to mimic menopause by ovariectomizing animals; 7,8 however, these have rarely taken into account the effect of aging and cessation of ovarian function. In any case, there is no normotensive animal model that exhibits hypertension with aging.…”
Section: Animal Model For the Study Of Postmenopausal Hypertensionmentioning
confidence: 99%